X-Ray Imaging Calibration for Fuel-Coolant Interaction Experimental Facilities - Journeau Christophe (EDP Sciences, 2021)
During a severe accident in either sodium-cooled or water-cooled nuclear reactors, jets of molten nuclear fuel may impinge on the coolant resulting in fuel-coolant interactions (FCI). Experimental programs are being conducted to study this phenomenology and to support the development of severe accident models. Due to the optical opacity of the test section walls, sodium coolant, and the apparent optical opacity of water in the presence of intense ebullition, high-speed X-ray imaging is the preferred technique for FCI visualization. The configuration of these X-ray imaging systems, whereby the test section is installed between a fan-beam X-ray source and a scintillator-image intensifier projecting an image in the visual spectrum onto a high-speed camera, entails certain imaging artefacts and uncertainties. The X-ray imaging configuration requires precise calibration to enable detailed quantitative characterization of the FCI. To this end, ‘phantom’ models have been fabricated using polyethylene, either steel or hafnia powder, and empty cavities to represent sodium, molten fuel and sodium vapor phases respectively. A checkerboard configuration of the phantom enables calibration and correction for lens distortion artefacts which magnify features towards the edge of the field of view. Polydisperse steel ball configurations enable precise determination of the lower limit of detection and the estimation of parallax errors which introduce uncertainty in an object’s silhouette dimensions. Calibration experiments at the MELT facility determined lower limits of detection in the order of 4 mm for steel spheres, and 1.7-3.75 mm for vapor films around a molten jet.